Ladle and In-mold Modification Methods for Obtaining Castings from Cast Irons with Various Graphite Morphology - Zakharchenko, E.V.; Shinsky, O.I.; Baglyuk, G.A.; Klimenko, S.I.; Kurovsky, V.Ya.; Sirenko, E.A.; Goncharov, A.L. (Наука та інновації, 2019)
Introduction. In the world practice of foundry, modification has reached the status of leading direction of research and applied work to improve the technological and service properties of structural cast irons. Problem Statement. Modifying treatment of liquid iron provides for not only the creation of certain types of modifiers, but also for the development of such methods for introducing modifier into the melt, which are adaptable to the conditions of foundries and take into account the requirements for specific groups of castings. Purpose. To develop a pilot technology for the modification of electric furnace melts of cast iron in unsealed ladle with removable bowl caver and casting molds using complex reagents in the form of pressed powder briquettes and lumpy fused master alloys for the production of castings with lamellar, vermicular and spherical graphite. Materials and Methods. The following materials have been used in the research: gray cast iron, as an object of research for modifying treatment, magnesium-lanthanum-containing lumpy and briquetted powder modifiers, as well as nitrogencontaining lumpy and briquetted powder modifiers to produce cast iron with various forms of graphite, depending on the requirements for castings. Results. A pilot technology for cast irons using pressed powder nitriding briquettes to increase twice the tensile strength of structural gray cast irons (from 200 MPa to 400 MPa) without alloying and heat treatment and a ladle process for modifying molten iron melts with lanthanum-containing modifiers have been developed. The prospects for the production of nitrated iron with vermicular graphite with a sulfur content of up to 0.1% wt. by re-melting the nitrogenous metal charge and fresh and rotary cast irons and therefore with the possible minimum additional introduction of nitrogen in the furnace or in the ladle or in the mold have been substantiated. Conclusions. The pressed powder composite modifiers are recommended as the most effective ones for the mentioned modifying methods, depending on the requirements for castings.